Upaya Peningkatan Hasil Belajar Melalui Metode Cooperative Script Pada Mata Pelajaran Akidah Akhlak Siswa Kelas VIII MTs Nur Bahri Bubun - Syahrul Kodrah, M. Hasbullah, Sri Mulyani, (Invention: Journal Research and Education Studies, 2021)
The background of this research is that the method or approach used in teaching Akidah Akhlak is less able to generate student motivation. To follow the Akidah Akhlak lessons, it is proven by the number of students who are still busy alone and busy joking with their classmates and also the student's learning activity is very low because the methods used in learning Akidah Akhlak are considered not to have reached the desired target due to teachers who are less successful in the learning process. teaching with several indicators, namely student learning outcomes are still low and the delivery of material is not in accordance with predetermined standard limits. The objectives of this research are: To determine the learning outcomes of students' Akidah Akhlak after applying the cooperative script method in class VIII MTs Nur Bahri Bubun. This research was conducted in the form of classroom action research. According to the type of research chosen, namely classroom action research, this research uses an action research model in the form of a spiral and from one cycle to the next. The results of this study are: The learning outcomes of students' Akidah Akhlak after applying the cooperative script method in class VIII MTs Nur Bahri Bubun, namely in the first cycle students who have a complete score of 20 students or 74.1% of 27 students and in the second cycle there is an increase of as much as 22 students who completed or 92.6%. In cycles I and II, there was an increase of 24.97%.